[Translated article] Tumor ablation and vertebral augmentation in the treatment of vertebral metastases: A multicenter study - M. Alfonso; R. Llombart; L. Gil; I. Martinez; C. Rodríguez; L. Álvarez; J. Gallego (Revista Española de Cirugía Ortopédica y Traumatología, 2023)
Introduction: Treatment of metastatic vertebral fractures without neural compression is performed with percutaneous cementation techniques. The increase in intratumoral pressure by these techniques can send tumor cells into the bloodstream. To prevent this dissemination and improve pain treatment, ablation techniques have been introduced that would allow the creation of a cavity in the tumor prior to cementation or directly necrosing the metastasis when its size is small. Material: We present the experience with ablation of two hospitals and two different ablation techniques. The first group used radiofrequency ablation (A) in 14 patients (26 vertebrae), 4 of whom underwent vertebral arthrodesis. The second group used microwave ablation (B) in 93 patients (129 lesions) without associated vertebral instrumentation. Results: In group A pain improvement in VAS was 7.7–2.6 at 6 weeks. There were no complications derived from the ablation. In most cases cementation was associated. In the group B pain improvement in VAS went from 6.8 to 1.7 at 6 weeks. Cementation was associated in all cases. There were no complications derived from the ablation. Conclusion: The association of ablation techniques with vertebral cementation is a safe technique that significantly improves the patient's pain and can help control the disease. Resumen: Introducción: El tratamiento de las fracturas vertebrales metastásicas sin compresión neural se realiza con técnicas percutáneas de cementación. El aumento de presión intratumoral por estas técnicas puede enviar células tumorales al torrente sanguíneo. Para evitar esa diseminación y mejorar el tratamiento del dolor se han introducido las técnicas de ablación que permitirían crear una cavidad en el tumor previo a la cementación o directamente necrosar la metástasis cuando el tamaño es pequeño. Material: Presentamos la experiencia con la ablación de dos hospitales y dos técnicas de ablación distintas. El primer grupo usó la ablación por radiofrecuencia (ARF) en 14 pacientes (26 vértebras) de los cuales en cuatro se asoció una artrodesis vertebral. El segundo grupo usó la ablación por microondas (AMO); 93 pacientes (129 lesiones) sin asociar instrumentación vertebral. Resultados: En el grupo de ARF la mejoría del dolor en la escala visual analógica (EVA) fue de 7,7 a 2,6 a las seis semanas. No hubo complicaciones derivadas de la ablación. En la mayoría de los casos se asoció la cementación. En el grupo de AMO la mejoría del dolor en EVA pasó de 6,8 a 1,7 a las seis semanas. En todos los casos se asoció la cementación. No hubo complicaciones derivadas de la ablación. Conclusiones: La asociación de las técnicas de ablación a la cementación vertebral es una técnica segura, que permite mejorar notablemente el dolor del paciente y puede ayudar al control de la enfermedad.